A Comprehensive Review on the Applications of Nanometal Additives in Fuels for Internal Combustion Engines - MOHAN, Udayakumar; SIVAMANI, Selvaraju (Engineering Transactions, 2025)
Nanometal additives have emerged as promising candidates for enhancing the performance and efficiency of internal combustion (IC) engines. The present review provides an overview of their applications and benefits  in IC engines. These additives, characterized by their nanoscale size and unique properties, offer advantages such as improved combustion kinetics, enhanced catalytic activity, and reduced emissions. By leveraging their high surface-to-volume ratios and tailored surface chemistry, nanometal additives facilitate more efficient fuel combustion, leading to higher engine efficiency and lower pollutant emissions. Also, this review highlights the importance of nanometal additives in addressing challenges related to fuel quality, combustion efficiency, and environmental impact in IC engines, paving the way for cleaner and more efficient engine technologies.